Canadian Publications in Library and Information Science: A Database of Research by LIS Academics and Practitioners in Canada - Sauvé, Jean-Sébastien; Hare, Madelaine; Krause, Geoff; Poitras, Constance; Riddle, Poppy; Mongeon, Philippe (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2025)
The aim of the Canadian publications in Library and Information Science (LIS) database is to help break down the silos in which the two main target audiences – LIS faculty members and academic librarians – conduct their research. As part of a larger project entitled “Breaking down research silos”, we created a database of research contributions by Canadian LIS researchers (academics and practitioners). This was motivated by a desire to make research by Canadian LIS scholars and practitioners more visible and foster collaboration between these two groups. The aim of this paper is to introduce the database, describe the process through which it was created, provide descriptive statistics of the database content, and highlight areas for future development.